Characterization of Staphylococcus aureus Isolates From Cystic Fibrosis Patients - KARAHASAN, AYŞEGÜL (My University, 2018)
ObjectiveStaphylococcus aureus is among the pathogens which colonizes and infects the respiratory tract of cystic fibrosis (CF) patients.This bacterium is the most prevalent pathogen in children and adolescents and replaced or co-existed with Pseudomonas aeruginosa in later periods of the disease.S. aureus produces various virulence factors including exotoxins, enzymes and cell wall proteins facilitating host cell binding (Hotterbeekx A, et al. Front Cell lnfect Microbiol. 2017; 3:106). In this study, we aimed to characterize the antimicrobial susceptibility profile and toxin producing capability of certain S.aureus isolates and cumulative antibiogram results of this pathogen obtained from our CF patients.MethodsTotal of 70 S.aureus isolated from lower respiratory tract samples of CF patients between 2016- October 2017 were included. MALDI-TOF MS (Vitek MS, bioMerieux, France) was used for bacterial identification. An automated system (VITEK 2 Compact, bioMerieux) was used to determine the antimicrobial susceptibility. Five enterotoxins (sea,seb,sec,sed and see), Panton-Valentine leukocidin (PVL;IukS/F) and toxic shock toxin-I (tst) encoding genes were investigated by PCR (Tekeli A, et al. Mikrobiyol Bul. 2009;43:1-10).ResultsAmong the 70 S.aureus isolates, 25 (35.7%) were methicillin-resistant (MRSA). Ali isolates wereresistant to penicillin; resistance rates for erythromycin, ciprofloxacin, levofloxacin, gentamicin,tetracycline, and clindamycin were 42.8%, 17.1%, 7.1%, 14.2%, 27.1%, and 10% respectively. Allisolates were susceptible to vancomycin and tigecycline. Cumulative antibiogram results of S.aureus isolates were shown in Table. PCR analysis for toxin genes revealed 12, 3 and 2 isolates were positive for sea, sec and sed genes, respectively. tst gene was detected in 26 isolates (37.4%), and 21 of the S. aureus isolates (30%) tested positive for the lukS/F genes.Conclusions S. aureus is one of the most common isolated pathogens in CF patients. We found that all the study isolates were resistant to penicillin, but sensitive to various antibiotics. Our results also demonstrated that toxic shock toxin-I and Panton-Valentine leukocidin coding genes were prevalent (37.4% and 30.0%, respectively) in our collection. Antibiotic susceptibility and virulence profiles further emphasise the importance of the characterization of S. aureus isolated in CF.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Mikrobiyoloji ve Klinik Mikrobiyoloji; Tıbbi Mikrobiyoloji; Medicine; Health Sciences; Fundamental Medical Sciences; Microbiology and Clinical Microbiology; Medical Microbiology; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Mikrobiyoloji; TIP, GENEL & DAHİLİ; MİKROBİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MICROBIOLOGY; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Mikrobiyoloji (tıbbi); Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; İmmünoloji ve Mikrobiyoloji (çeşitli); Yaşam Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Microbiology (medical); Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Microbiology; Immunology and Microbiology (miscellaneous); Life Sciences